UMKM Naik Kelas: Economic Strengthening Strategy Through Product Optimization to Enhance MSMEs Performance - Fitri, Raisa; Nora, Elifia; Anindya, Anastasia Ayu (Jurnal Pengabdian Masyarakat, 2024)
Purpose: Omah Singkong MSMEs focuses on processing frozen tubers and has significant potential in the local economy of Malang City. The purpose of this community service is to provide comprehensive assistance by utilizing technology, especially the vacuum sealer machine, to improve product quality and competitiveness and marketing strategies. Consequently, this MSMEs is expected to expand its market share, increase income, and become a pillar of a sustainable and inclusive local economy. Method: The following methods were used: 1) problem identification; 2) implementation of activities; and 3) program evaluation. These activities were carried out at the Omah Singkong MSMEs, Karangploso, Malang Regency. Practical Applications: The results of this community services activity are evident in the improved quality and competitiveness of Omah Singkong MSMEs products using the Vacuum Sealer machine to improve packaging efficiency and extend the shelf life of frozen products. Moreover, the provided managerial training has a positive impact by enhancing skills in operational management, stock management, and marketing strategies, preparing MSMEs to take a more active role in supporting local economic growth and improving the welfare of society. Conclusion: This community service program improved Omah Singkong MSMEs’ product quality and competitiveness through vacuum sealer technology and managerial training. These enhancements support market expansion, income growth, and the MSMEs’ role in Malang’s local economy.